The U-Shaped Association Between Serum Uric Acid and Red Blood Cell Distribution Width in Acute Ischemic Stroke - Rong, Ning; Zhao, Pei; Yang, Jin; Fan, Qing-Lei; Zhang, Qiang; Han, Zhi-Gang; Cai, Jian; Zhu, De-Sheng (Frontiers in Physiology, 2021)
Objective: U-shaped association between serum uric acid (SUA) and functional outcome has been found in acute ischemic stroke (AIS). However, it is unclear if SUA is associated with red blood cell morphology in AIS. This study aimed to determine the relationship between SUA and red blood cell distribution width (RDW) in AIS patients. Methods: A cross-sectional study including 438 consecutive AIS patients was conducted. SUA and RDW, a biochemical parameter that reflects the heterogeneity of red blood cell volume, were evaluated on admission. We evaluated the association between SUA and RDW through linear curve fitting analyses and two-piecewise regression analyses. Results: The association between serum SUA levels and RDW followed a U-shape in all patients. In female, the values of RDW significantly decreased with the increment of serum SUA (per mg/dL: β, -1.45; 95%CI: -2.15- -0.75, p<0.001) in patients with serum SUA<3.86 mg/dL, and increased with the increment of serum SUA (per mg/dL: β, 0.60; 95%CI: 0.22- 0.97, p=0.002) in patients with serum SUA≥3.86 mg/dL. Similar results were observed in male with the turning point of SUA=4.82 mg/dL. After adjusting for potential confounders, U-shaped association between SUA and RDW maintained in female, but no statistical significance maintained in patients with serum SUA≥4.82 mg/dL in male (p=0.206). Conclusion: In this sample of AIS patients, we found a U-shape relationship between serum SUA levels and RDW, with the turning point of SUA (3.96 mg/dL in female and 4.82 mg/dL in male) by threshold effect analysis.